Infografia interativa na redação: o processo de produção no Diário do Nordeste à luz da teoria do jornalismo - Silva, William Robson Cordeiro (2013)
The infographics historically experience the process of evolution of journalism, from the incipient models handmade in the eighteenth century to the inclusion of computers and sophisticated software today. In order to face the advent of TV against of the partiality readers of the printed newspaper, or to represent the Gulf War, where not allowed photography, infographics reaches modern levels of production and publication. The technical devices which enabled the infographics to evolve the environment of the internet, with conditions for the manipulation of the reader, incorporating video, audio and animations, so styling of interactive infographics. These digital models of information visualization recently arrived daily in the northeast and on their respective web sites with features regionalized. This paper therefore proposes to explore and describe the processes of producing the interactive infographics, taking the example of the Diário do Nordeste, Fortaleza, Ceará, whose department was created one year ago. Therefore, based on aspects that guide the theory of journalism, as newsmaking, filters that focus on productive routine (gatekeeping) and the construction stages of the news. This research also draws on the theoretical framework on the subject, in concepts essential characteristics of computer graphics, as well as the methodological procedures and systematic empirical observations in production routines of the newsroom who can testify limitations and / or advances